Resilience: A Right-Winger's Ploy? - Mykhnenko, V (Routledge, 2016)
It is often said that cities and regions, their populations, and their governance structures increasingly have to respond to major challenges and a vast range of contemporary risks resulting from environmental change, threats to national and international security, and an array of issues associated with international migration and growing global economic turbulence. In the short term, at least in the global North, local communities, cities, and regions have to tackle and mitigate the impact of the global financial and economic crisis. In the medium term, they ought to be equipped to manage the pressures of an ageing and declining population. In the long run, the capacity and systemic capabilities of the critical urban infrastructure in major population centres must be enhanced to cope with the potentially cataclysmic consequences of climate change. ‘Resilience’ is a conceptual framework which purportedly offers its adherents a set of mechanisms to confront these monumental challenges of the modern age.